Libraries, publishing houses and children’s literature on the net: an analysis from the perspective of reading promotion - Vila Carneiro, Zaida; Martín-Macho Harrison, Ana (Didáctica. Lengua y Literatura, 2022)
This paper offers a quantitative/qualitative comparison of the interaction that libraries and publishers of children’s literature establish with child and young readers through social networks. A quantitative analysis of their presence on social networks is accompanied by a qualitative description of the predominant trends in the use that these institutions, as promoters of reading, make of social networks. It studies the presence on social networks of the 15 publishers included in the directory of publishers of children’s literature of the National Library of Spain, as well as 19 Spanish public libraries ˗one for each autonomous region and city˗ whose presence on social networks is active, with profiles including activities and information aimed at children and adolescents. Examples of both good and improvable practices are pointed out.